2019
DOI: 10.1016/j.stem.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics Uncovers Glial Progenitor Diversity and Cell Fate Determinants during Development and Gliomagenesis

Abstract: The identity and degree of heterogeneity of glial progenitors and their contributions to brain tumor malignancy remain elusive. By applying lineage-targeted single-cell transcriptomics, we uncover an unanticipated diversity of glial progenitor pools with unique molecular identities in developing brain. Our analysis identifies distinct transitional intermediate states and their divergent developmental trajectories in astroglial and oligodendroglial lineages. Moreover, intersectional analysis uncovers analogous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
145
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(174 citation statements)
references
References 51 publications
16
145
0
Order By: Relevance
“…Here we show that classical glioma TME components such as microglia/macrophages, astrocytes and OPCs are present in xenografted tumors, indicating that tumor cell interactions with the TME remain active in PDOX. Of note, we observe a similar transcriptomic shift in tumor-associated microglia/macrophages as described in GBM patients 59,91 . It remains to be determined to what extent these models will be amenable to immunotherapeutic studies targeting tumor-associated microglia/macrophages.…”
Section: Discussionsupporting
confidence: 82%
“…Here we show that classical glioma TME components such as microglia/macrophages, astrocytes and OPCs are present in xenografted tumors, indicating that tumor cell interactions with the TME remain active in PDOX. Of note, we observe a similar transcriptomic shift in tumor-associated microglia/macrophages as described in GBM patients 59,91 . It remains to be determined to what extent these models will be amenable to immunotherapeutic studies targeting tumor-associated microglia/macrophages.…”
Section: Discussionsupporting
confidence: 82%
“…Human brain cancer is a devastating disease, with a median survival of less than two years for glioblastoma. Recent work using single-cell RNA-sequencing to determine the cellular composition of glioblastoma has suggested that these tumors reflect a reversion to an embryonic cell state resembling neural progenitors, OPCs and/or immature astrocytes 24,43,44 . To unambiguously test this hypothesis, we compared human brain tumor data -comprising five glioblastoma samples and one anaplastic astrocytoma 45 -with a reference cell type catalog constructed by merging the developmental cell atlas of this paper with our previous adolescent brain cell atlas 22 (Methods and Extended Data Figure 9).…”
Section: • Metadatamentioning
confidence: 99%
“…105 Several groups consistently reported that the OPC-like cellular population constitutes the actively proliferating fraction of glioma cells. 74,97,105,106 In addition, it will be interesting to elucidate if cellular subpopulations differ in the extent of therapy resistance and network integration.…”
Section: Neurodevelopmental Origins Of Gliomasmentioning
confidence: 99%